Economic Policy Uncertainty and ASEAN-6 Exchange Rates: A Long-Run Panel ARDL Analysis - Munandar, Aris (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study examines the effect of U.S. and global Economic Policy Uncertainty (EPU) on the exchange rates of ASEAN-6 countries (Indonesia, Malaysia, Philippines, Singapore, Thailand, Vietnam) using balanced monthly panel data from January 2010 to December 2024. Employing a Panel Autoregressive Distributed Lag (ARDL) model estimated using the Pooled Mean Group (PMG) estimator, the empirical findings demonstrate that heightened U.S. and global EPU induce long-run appreciation of ASEAN-6 currencies. Consequently, the research underscores the necessity for ASEAN-6 central banks to proactively monitor U.S. and global EPU trends and adjust monetary or foreign exchange operations to mitigate export competitiveness erosion and inflationary pressures, while governments should support exporters with diversification strategies to maintain competitiveness amidst sustained currency appreciation driven by external uncertainty. Keywords: Economic Policy Uncertainty; Exchange Rates; ASEAN-6; Currency Appreciation; Panel ARDL